2018
DOI: 10.3390/cli6010016
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Thermal Hot and Cold Spots in Urban Areas in Support of Mitigation Plans to Counteract Overheating: Application for Athens

Abstract: Mitigation plans to counteract overheating in urban areas need to be based on a thorough knowledge of the state of the thermal environment, most importantly on the presence of areas which consistently demonstrate higher or lower urban land surface temperatures (hereinafter referred to as "hot spots" or "cold spots", respectively). The main objective of this research study is to develop a methodological approach for the recognition of thermal "hot spots" and "cold spots" in urban areas during summer; this is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…Assessments of climate change on flood risk can be very uncertain for many reasons, such as climate model choice ( Deser et al, 2012 ), downscaling and bias-correction procedures, hydrological model choice and parameter estimation ( Donnely et al, 2017 ). Alfieri et al (2018) concluded that uncertainty from climate projections is the main driver of uncertainty when assessing future flood risk under global warming because the model error due to the flood component of the model is smaller than the differences due to alternative climate change scenarios. Another source of uncertainty arises when only a small number of years of flooding are simulated: many studies of future flood risk based on climate models output have been limited to simulations of no more than 100 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessments of climate change on flood risk can be very uncertain for many reasons, such as climate model choice ( Deser et al, 2012 ), downscaling and bias-correction procedures, hydrological model choice and parameter estimation ( Donnely et al, 2017 ). Alfieri et al (2018) concluded that uncertainty from climate projections is the main driver of uncertainty when assessing future flood risk under global warming because the model error due to the flood component of the model is smaller than the differences due to alternative climate change scenarios. Another source of uncertainty arises when only a small number of years of flooding are simulated: many studies of future flood risk based on climate models output have been limited to simulations of no more than 100 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study which considers natural correlation between events, Jongman et al (2014) found an almost five-fold increase in annual loss by 2050 for a 3 °C global warming, whereas Alfieri et al (2015) found for the same period an increase of 4 to 8 times for a 4 °C global warming scenario. More recently, Alfieri et al (2018) reported changes in annual loss for three warming levels (1.5, 2 and 3 °C) and three independent studies to be roughly in a range between 2 and 4 times that of the present. The latter three studies do not include the effect of future socio-economic changes on population, economy, and land use, so flood risk was estimated assuming present-day exposure and vulnerability.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This index has been determined by Baker et al (2004), and after its inventors is called the R-B Index (or RBI). This index has been calculated with the following formula [1]:…”
Section: Methodsmentioning
confidence: 99%
“…In the recent years, there have been a number of studies conducted on the influence of climate change on water resources (Pekarova et al, 2006;Stahl et al, 2010;Dobrovol'skii, 2018). In the literature on the subject, one may find publications regarding projections of future climate changes for the region of Europe (IPCC 2013; Alfieri et al, 2018). Climate predictions for Poland expect further warming and continuation of already observed changes in amounts of precipitation and precipitation's spatial and seasonal distribution (Szwed et al, 2010;Osuch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%